Governance of educational trajectories in Slovenia - Ule, Mirjana (Annales. Series historia et sociologia, 2013)
The aim of this article is to analyse the relationships among the different actors involved in educational trajectories in Slovenia, to understand their different perspectives, and to describe the constellations of factors of relevance, responsibility and support in students educational trajectories. The research instruments are semi-structured interviews with different actors (students, parents, teachers, counsellors, experts). Since the 1970s, Slovenia has managed to strongly raise the educational level of especially disadvantaged groups of young people, such as women and children from socially weaker families and milieus. This kind of system has supported the social integration of disadvantaged, socially vulnerable and handicapped groups of young people. However, today and especially in the light of the increasingly serious economic and social crisis this system is under threat from both the outside and inside. Externally, it is threatened by the lack of financial and material resources, the neoliberal austerity policy and the weakening of the institutions of the welfare state; internally, it is weakened by the imbalance between key educational agents, students, parents, teachers and experts. While the external pressures are weakening the strength and position of schools as the key educational institutions, the internal pressures are diminishing the professional authority of teachers and their professional competencies.
Keywords: Družbena integracija; Education; Individualizacija; Individualization; Izobraževanje; Slovenia; Slovenija; Social integration